Participatory health through behavioural engagement and disruptive digital technology for postoperative rehabilitation: protocol of the PATHway trial. Issue 1 (17th January 2021) - Wang, Xia; Hunter, David J; Robbins, Sarah; Capistrano, Sarah; Duong, Vicky; Melo, Luciano; Harris, Anthony; Ferreira, Manuela
Abstract : Introduction: Postsurgical rehabilitation is critical for optimal recovery in people undergoing orthopaedic surgery. Currently, knee and lumbar spine postsurgical care is not standardised, economically sustainable, nor based on quality evidence, contributing to substantial clinical variation, poor outcomes and increasing healthcare costs. This protocol describes the design of a randomised controlled trial aiming to evaluate the effectiveness and cost-effectiveness of a postsurgical clinical pathway augmented by disruptive technology and compared with standardised rehabilitation alone, in decreasing pain and improving function after total knee replacement (TKR) or lumbar laminectomy (with or without fusion). Methods: An assessor-blinded, parallel group, randomised controlled trial will be conducted to recruit 204 consenting participants (102 per arm) of whom 50% are undergoing TKR and 50% lumbar surgery. The intervention group will receive a 6-month technology-enabled rehabilitation package in addition to usual postsurgical care. The package includes (1) an exercise program delivered via the Physitrack app on the iPad, (2) a health-coaching program delivered via video calls and motivational messages, (3) use of physical activity tracker with goal setting and motivational reminders (Fitbit). For those undergoing TKR, the intervention will also include knee joint range of motion self-monitoring via the Goniometer app. The control group will receive usual postsurgical care. Participants will be followed up at 3, 6 and 12 months from the enrolment date. The primary outcome is pain measured with the Numerical Rating Scale at 3 months. Secondary outcomes include pain-related disability, quality of life, computer self-efficacy, physical activity participation and sedentary behaviour. Data analysis will be blinded and by intention-to-treat. A trial-based cost-effectiveness analysis will determine the potential incremental cost per quality-adjusted life-year gained. Ethics and dissemination: This protocol is approved by the human research ethics committee of the University of Sydney. Dissemination will occur through lay summary, infographics, conferences and journal publications. Trial registration number: ACTRN12618001448235.